Emissions Trading Regimes and Incentives to Participate in International Climate Agreements - Barbara Buchner; Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper analyses whether different emissions trading regimes provide different incentives to participate in a cooperative climate agreement. Different incentive structures are discussed for those countries, namely the US, Russia and China, that are most important in the climate negotiation process. Our analysis confirms the conjecture that, by appropriately designing the emission trading regime, it is possible to enhance the incentives to participate in a climate agreement. Therefore, participation and optimal policy should be jointly analysed. Moreover, our results show that the US, Russia and China have different most preferred climate coalitions and therefore adopt conflicting negotiation strategies.
Keywords: C72; H23; Q25; Q28; 330; Agreements; Climate; Incentives; Negotiations; Policy; Klimaschutz; Umweltabkommen; Anreiz; USA; Russland; China; Emissionshandel